Socio-Economic Conditions of Coffee Farmers in Blang Gele Village, Central Aceh District - Penona. DA, Kin; Fitrah, Hariki; Rahmi Novalita, Rahmi Novalita (Sumatra Journal of Disaster, Geography and Geography Education, 2023)
The aim of this research is to describe the socio-economic conditions of coffee farmers in Blang Gele village, Bebesan District, Central Aceh Regency. The type of research is qualitative research. The research informants were coffee farming communities in Blang Gele village. The technique for taking informants uses snowball sampling technique. Data collection techniques use observation, interviews and documentation. Data analysis techniques include data reduction, data display, and drawing conclusions. The research results show that the socio-economic conditions of coffee farmers are relatively good when viewed from the perspective of education, income, health and housing. This research produced a specific finding, namely the mangolo culture, which is a tradition carried out from generation to generation by coffee farming communities in cultivating coffee plants. Mangolo is a social tradition that involves village communities gathering to do coffee picking or other work together and taking turns. Mangolo culture is a transaction system by exchanging services in coffee farming. Mangolo culture has meaning and value for the farming community in increasing the sense of solidarity and care between fellow coffee farmers.